2013
DOI: 10.1097/iae.0b013e31827c53a0
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant Macular Edema After Intravitreal Bevacizumab Is Responsive to an Intravitreal Dexamethasone Implant in Retinal Vein Occlusion

Abstract: A subset of patients do not have resolution of macular edema after treatment with intravitreal bevacizumab. Such patients may respond to treatment with an intravitreal dexamethasone implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 9 publications
2
26
1
Order By: Relevance
“…It is important to point out that persistent CME in this study was defined as CME nonresponsive or partially responsive to a minimum of 2 bevacizumab injections and that the average duration of CME prior to injection was 11.08 ± 8.82 weeks. The persistence of CME in this study is therefore relatively short compared to our study and the other studies described above [32]. …”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…It is important to point out that persistent CME in this study was defined as CME nonresponsive or partially responsive to a minimum of 2 bevacizumab injections and that the average duration of CME prior to injection was 11.08 ± 8.82 weeks. The persistence of CME in this study is therefore relatively short compared to our study and the other studies described above [32]. …”
Section: Discussionmentioning
confidence: 44%
“…There is little evidence in the published literature of the effect of DEX-DDS in the treatment of edema persisting following other treatments [28,29,30,31,32,33]. The purpose of our study was to examine the effect of DEX-DDS in patients with severely recalcitrant CME that had a poor or short-term response to other treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…16 The group with fluid at 3 months will be further categorized using the definition proposed by Sharareh et al into those who have less than a 1% reduction in MO after 3 injections (the non-responders) and those who respond with at least a 10% reduction in MO (the partial responders). 27 Patients showing no fluid activity (early responders) after 3 monthly injections should be followed up monthly and injected using a PRN protocol for the first year and with gradual monthly extensions of the follow-up period during the second year to maintain gains. Patients showing residual fluid at 3 months should be categorized into partial or non-responders.…”
Section: Discussionmentioning
confidence: 99%
“…To further stratify this group of poorly responsive patients we suggest the definition used by Sharareh et al that suggested that patients who have o1% reduction in MO after injections are to be deemed non-responders and patients who respond with at least a 10% reduction in MO to be categorized as partial responders. 27 With that concept in mind we will explore some of the alternate treatment modalities that can be used in patient deemed nonresponsive or partially responsive after three loading doses of anti-VEGFs.…”
Section: Alternate Treatment Regimensmentioning
confidence: 99%
See 1 more Smart Citation